Marketing model for increasing the export potential of the enterprise - To’raev Shokhrukh Khalimovich (THE INNOVATION ECONOMY, 2026)
This scientific article is devoted to the issues of using the marketing model to increase the export poten tial of enterprises. The marketing model is a set of strategic tools and methods used by companies to successfully operate in the market. This is a model designed to deliver a product or service to consumers, sell it and meet their needs. This model also organizes a clear and well-thought-out system of work of marketing departments to achieve specific goals set by the enterprise and meet the needs of the target market. To do this, it is necessary to manage the marketing process, that is, correctly analyze market opportunities, select target markets, conduct marketing research and events.